Comportamentos de risco a saúde em estagiários dos cursos da área da saúde de uma universidade pública - COSTA, Juliana Carline Abreu Martins (2021)
Health risk behaviors are known to threaten health and reduce the quality of life. This is a quantitative and transversal study that aimed to analyze the health risks behavior prevalence on interns of health courses of Maranhão Federal University. As an inclusion criterion, it was selected regularly registered interns of their last academic year from the following courses: Physical Education, Pharmacy, Medicine, Nutrition, and Odontology. Due to the Covid Pandemic, the school year was atypical, resulting in a reduction in the number of interns. The data collection was done during September to December of 2020. The sample was composed of 31 interns. It was Applied the Youth Risk Behavior Survey (YRBS) that analyses health risk behaviors, healthcare behavior and the perception of the relation with family, friends, and university. It was applied descriptive statistics and we used the chi-square test of Pearson and chi-square to verify the association of the health risk behaviors. To analyze the data, it was used Statistical Package for the Social Sciences 10. It was verified that most interns were women – 22 (70,9%), between 23 25 years old – 20 (60,5%), and self-reported skin color white – 12 (38,7%). It was verified an association between age and risk behavior of riding a motorcycle without using a helmet or rarely using it (p X 2 = 0,43), prevailing male participants (pX 2 = 0,37). The courses of Pharmacy and Physical Education showed most health behavior risks pX 2 = 0,007. There is a gradual increase in behavior related to suicide attempts, 25,80% (n=8) of participants affirm that they “think seriously in committing suicide”, 16,12% (n=5) said they “planned to commit suicide”, and one intern effectively tried to do it 3,22% (n=1). There is a significant association between tobacco use and gender, p X2 0,007, prevailing male participants (28) 88,89%. All interns from the 8th study (100%) reported consuming alcohol during public events. It was observed health risk behavior related to the frequency of male sexual activity with a high number of sexual partners, with (10) 33,33% from age group 29 to 30 years old in sexual activities with six to more people. This health risk behavior was related to the Physical Education course through the chi-square of Pearson with pX2 0.03. It was reported sexual activities with more than two people in participants from all courses. Health risk behavior was also associated with a sedentary lifestyle. This study shows that college students are vulnerable to health risk behaviors such as alcohol consumption and other psychoactive substances, irresponsible drive behavior, sadness, sexual relations, and sedentary lifestyle. These results contributed to creating a video to guide and inform about health risk behaviors.